2002
DOI: 10.1002/cfg.199
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous array analysis in Pinaceae: hybridization of Pinus taeda cDNA arrays with cDNA from needles and embryogenic cultures of P. taeda, P. sylvestris or Picea abies

Abstract: Hybridization of labelled cDNA from various cell types with high-density arrays of expressed sequence tags is a powerful technique for investigating gene expression. Few conifer cDNA libraries have been sequenced. Because of the high level of sequence conservation between Pinus and Picea we have investigated the use of arrays from one genus for studies of gene expression in the other. The partial cDNAs from 384 identifiable genes expressed in differentiating xylem of Pinus taeda were printed on nylon membranes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 23 publications
1
24
0
1
Order By: Relevance
“…We have previously demonstrated that Norway spruce cDNAs hybridize strongly with arrayed loblolly pine cDNA, thus allowing pine arrays to be used to assay spruce gene expression (Van Zyl et al 2002). To further investigate the hybridization efficiencies of the Norway spruce transcriptome towards the heterologous array, we have compared the sequence identity among Pinus and Picea species for genes used in qRT-PCR to validate the microarray results.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously demonstrated that Norway spruce cDNAs hybridize strongly with arrayed loblolly pine cDNA, thus allowing pine arrays to be used to assay spruce gene expression (Van Zyl et al 2002). To further investigate the hybridization efficiencies of the Norway spruce transcriptome towards the heterologous array, we have compared the sequence identity among Pinus and Picea species for genes used in qRT-PCR to validate the microarray results.…”
Section: Resultsmentioning
confidence: 99%
“…Two-dimensional gel electrophoresis-based proteomic approaches have been applied to investigate molecular changes during SE in several species (Choi and Sung, 1984;Gianazza et al, 1992;Reinbothe et al, 1992;Boyer et al, 1993;Pedroso et al, 1995;Yoshida et al, 1995;Dodeman and Ducreux, 1996;Giroux and Pauls, 1996;Dodeman et al, 1998;Sallandrouze et al, 1999) with limited success. Large-scale transcription analyses of embryogenesis have also been reported in several species (Giroux and Pauls, 1997;van Zyl et al, 2002van Zyl et al, , 2003Stasolla et al, 2003;Thibaud-Nissen et al, 2003;Stasolla et al, 2004).…”
mentioning
confidence: 96%
“…Microarray analysis has previously been used for identifying genes involved in cell wall biosynthesis during xylogenesis in P. taeda (Whetten et al, 2001). Recently, we showed that arrays from P. taeda can be used for studying gene expression in Picea abies and Pinus sylvestris (van Zyl et al, 2002a(van Zyl et al, , 2002bStasolla et al, 2003). At present, the possibility of sampling single cells or a small number of cells, and also obtaining synchronized populations of cells, is restricted (Hertzberg et al, 2001;van Zyl et al, 2002a).…”
mentioning
confidence: 99%